Catalytic Degradation of Polystyrene: Modeling of Molecular Weight Distribution - Gianoglio Pantano, Ioana Agustina (2011)
Two of the most abundant polymers in household waste streams, PS and PE, may be recycled by compatibilization through a Friedel-Crafts alkylation. This reaction produces a graft copolymer PE-g-PS that improves the properties of the blend, but simultaneously degrades PS chains. Since the copolymer efficiency as a compatibilizer depends both on the molecular weight and MWD of its two blocks, the operating conditions for the copolymer synthesis must be carefully tuned. To aid in this task, we present a preliminary mathematical model that focuses on the effect of the catalyst and cocatalyst of the Friedel-Crafts alkylation on the MWD of the PS chains. The model's predictions are shown to agree with experimental data. The evolution of the complete MWD of PS subjected to Friedel-Crafts alkylation during reactive processing of thermoplastics from waste streams is modeled. This is the first step towards the development of a complete description of the graft reaction that will aid in the tuning of appropriate processing conditions.